Determination of oleic acid in sunflower seeds by infrared spectroscopy and multivariate calibration method - Cantarelli, Miguel Angel (2009)
A method for the determination of oleic acid in sunflower seeds is proposed. One hundred samples of sunflower seeds were analyzed by near-infrared diffuse reflectance spectroscopy (NIRDRS). The direct measures were realized in ground and sifted seeds. The PLS multivariate calibration model was obtained using first derivate absorbance values as response matrix, while the oleic acid concentration matrix was obtained analyzing the seed samples by gas chromatography with a flame ionization detector (GC-FID). The NIRDRS-PLS model was validated externally using unknown samples of sunflower seeds. The accuracy and precision of the method was evaluated using GC as reference method. The following figures of merit (FOM) were obtained: LOD = 3.4% (w/w); LOQ = 11.3% (w/w); SEN = 8 × 10-5; SEL = 0.15; analytical sensibility (γ) = 1.5 and linear range (LR) = 18.1-89.2% (w/w). This method is useful for the fast determination of oleic acid in sunflower seeds and for quality control of raw materials.